A new approach to migrations: communities-on-the-move as assets. Issue 1 (2nd January 2019) - Parrilli, Mario Davide; Montresor, Sandro; Trippl, Michaela
ABSTRACT: This paper proposes a novel interpretive framework for studying migration and its implications in terms of innovation, entrepreneurship and regional development. We suggest that migration patterns and their impact should be analyzed through the lens of communities on the move (CoM): cultural communities marked by their own social capital, that is, shared values and network ties, which provide tacit knowledge and opportunities to their members and facilitate their integration in their host regions and countries. CoM have a strong influence on migrants' well-being and their capacity to produce innovation and entrepreneurial impact that promote the development of the host regions.